Increasing Student Activities and Learning Outcomes in Mathematics Learning Using the PINTAR Model in Banjarmasin City Elementary Schools - Zefri, Muhammad; Jannah, Fathul (Journal Of Foreign Language Learning and Teaching, 2024)
This research aims to find out how much influence the PINTAR learning model has on increasing activity, critical thinking skills and student learning outcomes in mathematics learning for students at SDN Pemurus Dalam 2 Banjarmasin. In this research, the method used is a qualitative approach and the type of research used in this research is classroom action research (PTK). In this research, the data collection instrument used was observation. Based on the results of this research, it can be concluded that the application of the PINTAR learning model influences increased activity, critical thinking skills, and student learning outcomes in mathematics learning for students at SDN Pemurus Dalam 2 Banjarmasin. Based on the results of the analysis, it shows that student activity increased by 56.25%, student critical thinking skills increased by 62.5%, and student learning outcomes increased by 43.75%. This proves that there is a positive influence from the PINTAR learning model on increasing activity, critical thinking skills, and student learning outcomes. With the SMART learning model, it is hoped that students will become more interested in participating in learning activities so that they have good qualities in becoming the next generation in the future